Penegakan Hukum Atas Pembajakan Kapal Indonesia Di Perairan Filipina - Erika Reski Alifatul Muafidah (Lentera Hukum, 2016)
Ship hijacking is a maritime crime generally committed in territorial waters. It often happens in Indonesia and the Philippines especially border areas of both countries (Malaysia – Philippines) makes other ASEAN countries feeling worried because it is closely related to the aspect of security. Those cases had a serious impact on international shipping towards other foreign and domestic vessels. For that reason, we are going to analyze solving the problems mainly crimes committed onboard vessels such as boat piracy on the Indonesia-Philippines frontier. This becomes a very serious problem and has big impacts on the International society. Consequently, the main point of this journal is to find out efforts will be made to overcome these problems, jurisdiction which is used to solve the problems and the crew protection KEYWORDS: Ship Hijacking,Piracy, Enforcement.